INTERPRETASI STAF PADA BAHASA MOTIVASI PIMPINAN (Studi Komunikasi Internal Perpustakaan Nasional) - Ade Farida (MediaKom : Jurnal Ilmiah Komunikasi, 2017)
This article based on the study of Leader Motivating Language interpreted by staff of the Indonesian National Library in their daily internal communication to achieve the organization strategic vision. The study extends the Motivating Language Theory (MLT) as a model and framework in finding information on the MLT’s values that staff experienced in day to day working with their leader. Most of MLT’s were studied in the West using survey as research method. This study was using deep interview of six senior staff in the organization that has significant role in the organization strategic vision goals. Result of this study showed that MLT’s used by the leader in this organization was slightly different compared to the previous research related to organizational culture for the government institution, personal influence as an Indonesian or Asian culture that more collective then individualist, and gender bias as responded to leader motivation language.Keywords: motivating language theory, leadership, internal communication